2014
DOI: 10.1080/07448481.2014.917652
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Sleepiness, Poor Sleep Quality, Eveningness Chronotype, and Common Mental Disorders Among Chilean College Students

Abstract: Objectives To evaluate whether daytime sleepiness, poor sleep quality and morningness and eveningness preferences are associated with common mental disorders (CMDs) among college students. Methods A total of 963 college students completed self-administered questionnaires that collected information about socio-demographic characteristics, sleep quality characteristics, CMDs, and other lifestyle behaviors. Results The prevalence of CMDs was 24.3% (95% CI: 21.5-27.1%) among all students. Prevalence estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 36 publications
4
21
0
9
Order By: Relevance
“…Further, future research may consider investigating other factors that affect university students' sleep hygiene practices. For example, a research showed that approximately 10% of college students prefer eveningness chronotype [63]. This sleeping practice not only violates healthy sleep hygiene practices, but also increases individuals' daytime sleepiness [63].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, future research may consider investigating other factors that affect university students' sleep hygiene practices. For example, a research showed that approximately 10% of college students prefer eveningness chronotype [63]. This sleeping practice not only violates healthy sleep hygiene practices, but also increases individuals' daytime sleepiness [63].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…For example, a research showed that approximately 10% of college students prefer eveningness chronotype [63]. This sleeping practice not only violates healthy sleep hygiene practices, but also increases individuals' daytime sleepiness [63]. It is also suggested that the use of electronic devices, exercise frequency, perceived stress, and alcohol and drug use are common factors causing poor sleep among young adults [64].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…One study indicated that daytime somnolence is associated with a 3.5-fold increased likelihood of presenting common mental disorders (CMD), including anxiety, mood disorders and eating disorders, behaviors related to the aforementioned 26 .…”
Section: Sleep Disorders and Anthropometric Measures In Chilean Univementioning
confidence: 99%
“…At the time, people showed less feeling and consciousness of external environment and low alertness and did not easily present instant responses to environmental changes and stimuli. Sleep quality was a complicated physiological health issue, which involved in broad factors, including individual physiological health, genetic factors, emotion and psychology, family and social interpersonal relationship, and physiological characters (Concepcion et al, 2014). Good-quality sleep refers to an adult continuously sleep 6-8 hours per day with sleep latency less than 30min, sleep efficiency above 85%, and sleep…”
Section: Sleep Qualitymentioning
confidence: 99%